Effects of pulmonary rehabilitation on exercise capacity and disease impact in patients with chronic obstructive pulmonary disease and obesity. Issue 2 (June 2018) - Broderick, J.; Mc Grath, C.; Cullen, K.; Talbot, D.; Gilmor, J.; Baily-Scanlan, M.; O'Dwyer, T.
Abstract: Objectives: To explore the influence of obesity on outcomes of exercise capacity and disease impact in patients with chronic obstructive pulmonary disease (COPD) in response to pulmonary rehabilitation (PR) and to compare outcomes to those of normal weight and overweight counterparts. Design: Secondary data analysis of clinical database. Setting: St. James's Hospital, Dublin, Ireland. Participants: 155 participants with a primary diagnosis of COPD who completed a PR programme between 2012 and 2014. Main Outcome Measures: Exercise capacity evaluated using the Six Minute Walk Test (6MWT) and the COPD Assessment Test (CAT) evaluated disease impact. Results: Walking distance in the 6MWT improved significantly [mean difference of 55 m (95% CI: 42 to 68; p < 0.001)] and similarly [ F (2, 92) = 1.434, p = 0.24] across all BMI categories, although the level of improvement reached clinical significance in the normal/underweight and overweight categories only. Disease impact on the CAT score improved across all body mass index (BMI) classifications by 2.3 points (95% CI: 0.9 to 3.6; p < 0.050) which reached clinical significance and did not vary across BMI categories [ F (2, 80) = 0.534, p = 0.58]. Conclusion: Exercise capacity and self-report disease impact of individuals with COPD improved similarly in response to PR irrespective of BMI.